The influence of service quality and trust on customer satisfaction - Benius, Benius; Raysharie, Puput Iswandyah; Roy, Ignatius Hapiktoran; A, Vioni; Wani, Yesra; Meilyadina, Yessyka; Yetno, Yetno; Sepditami, Yuafni; Tamil, Yuyun; Zahra, Zahra (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2024)
This comprehensive examination meticulously illustrates the profound ramifications of trust and the caliber of administration on consumer satisfaction, thereby shedding light on the intricate dynamics at play. It is evident that there exist both notable differences and significant similarities among the various journals that have been scrutinized, as well as the diverse perspectives that each of these scholarly publications presents. In addition to delving into several critical aspects concerning the constructs of trust and administration quality, a multitude of viewpoints will be explored in depth and with great consistency throughout the course of this Research Journal. The Learning Writing Research Methodology is employed as the primary approach for the systematic collection of data within this Research Journal, ensuring a robust analytical framework. This methodological approach aggregates information from a variety of distinct published journals, which are then synthesized into a singular comprehensive journal that will be subjected to thorough analysis and interpretation in this Research Journal. Through this rigorous examination, the study aims not only to contribute to the existing literature but also to foster a deeper understanding of the intricate relationships between trust, administration quality, and the resultant levels of consumer satisfaction. Ultimately, this research endeavors to illuminate the complexities of these interrelationships, offering valuable insights for both academics and practitioners in the field